(untitled) (Vietnam Journal of Community Medicine, 2026)
The study collected all serological test results from 190,090 patient visits at the Specialized Clinic of the Institute of Malaria, Parasitology, and Entomology in Quy Nhon from January 2023 to December 2024 to describe the seropositivity for parasites and investigate some related factors. The results showed that the seropositivity rate for at least one type of parasite was 20.6%. Among these, pork tapeworm (9.4%) and large liver fluke (7.9%) had the highest seropositivity rates, while amoeba and thorny-headed worm had the lowest rates at 2.5% and 4.4%, respectively. The rate of single infection among subjects with seropositivity for parasites was 79.4%. The most common age group for subjects with seropositive parasites was over 30 years old (22.0% for the 31-60 age group and 23.1% for those over 60). Females had a higher rate of seropositive parasites than males (21.8% vs. 18.9%, p<0.001). According to the multivariate logistic regression model, the factors: year of examination, age group, gender, and place of residence were associated with the rate of seropositive parasites (p<0.001).